PERAN TEKNOLOGI DIGITAL TERHADAP PERKEMBANGAN TEORI BELAJAR BAHASA: SEBUAH STUDI PUSTAKA - Abner Tolayuk; Muhammad Sahrir Aras (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study employed a literature review method, examining various scientific sources, including books, reputable journal articles, and research findings relevant to the topic of digital technology and language learning theory. Data collection was conducted through a literature search in academic databases, followed by descriptive qualitative analysis by identifying related concepts, findings, and research trends. The study's findings indicate that digital technology plays a significant role in enriching and transforming approaches to language learning theory and technology-based collaborative learning. Various digital platforms, artificial intelligence-based applications, and online learning media enable the language learning process to be more interactive, flexible, and learner-centered. Furthermore, digital technology also encourages the emergence of language learning models that are more adaptive to learner needs in the era of globalization. Thus, digital technology not only functions as a learning aid but also becomes a crucial factor in the development of modern language learning paradigms and theories.